The Effect of Using Different Bait on the Catch of Mangrove Crabs (Scylla sp) on Bubu Payung Fishing Equipment in Sapat Village, Indragiri Hilir Regency, Riau, Indonesia - Maulana, M Hafiz; Isnaniah, Isnaniah; Zain, Jonny (Jurnal Perikanan dan Kelautan, 2024)
Bubu is a passive fishing tool that works by trapping. Over time, a modification known as the bubu payung emerged, which is easy to obtain at an affordable price. This research was conducted in November 2023 over ten days in the waters of the Parit 18 River in Sapat Village, Kuala Indragiri District, Indragiri Hilir Regency. The method used in this research was experimental fishing, employing three types of bait: malong, coconut cake, and coconut pulp. Data analysis was performed using the t-test with SPSS 27.0.1. The results showed no significant difference in the catch of malong bait, coconut cake, or coconut dregs. According to the calculations, bait comparison A t-value (malong bait and coconut cake) (0,294) < t-table (2,306), bait comparison B (malong bait and coconut dregs) t-value (0,385) <t-table (2,306), and bait comparison C (coconut cake bait and coconut dregs bait) t-value (0,081) <t-table (2,306). Therefore, bubu payung can effectively catch mangrove crabs and bycatch